Gambiarras, Quilombos and Pachamama: Democratic Innovations and Assemblage Theory from Latin American Practices - Motta, Filipe Mendes; Mendonça, Ricardo Fabrino; Veloso, Lucas; Magalhães, Bruno Dias (Theoria (Pietermaritzburg), 2025)
The theory of assemblage has been increasingly influential in contemporary political theory and the democratic innovations debate. This perspective has propelled greater attention to extra-human entities in politics and a sensitivity to capture complex and non-linear relationships between these entities. The article seeks to expand the conceptual debates within the assemblage perspective, by exploring three Latin American conceptual contributions. We refer here to the concepts of gambiarra, quilombo, and Pachamama, which bring contributions that can enrich investigations conducted from assemblage perspectives. Gambiarra allows for considering the creative and risky potentials of contingent and unplanned practices. Quilombo contributes to thinking about the intersection between care and resistance in practices of articulation that recreate common possibilities of existence. Finally, Pachamama helps to redefine the centrality of extra-human entities in understanding politics.